HUBUNGAN LAMA PENGGUNAAN KB IUD DENGAN KADAR HB PADA AKSEPTOR KB IUD - Nur Hidayatul Ainiyah; Syuhrotut Taufiqoh; Enny Juniati (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
The IUD is the primary choice in the recommended long-term use of contraception. IUDs are widely used by women of childbearing age 20-35 years and have bleeding complications. This bleeding can cause a decrease in haemoglobin levels, so it is at risk of causing anemia. This research is analytical research with a cross-sectional design. This study aimed to determine the relationship between the duration of the IUD use and haemoglobin levels in family planning acceptors in the Tanah Kedinding Surabaya Health Center work area in 2020 with a sample of 11 IUD acceptors. Based on the results of the study, it was found that from the 11 respondents studied, 8 respondents (72.72%) were women of childbearing age users of long-term use IUDs, there were 5 people (62.50%) were anemic and as many as 3 respondents (27.27%) who were not anemic. Meanwhile, of the 3 (27.27%) women with IUDs using short-term IUDs, one respondent (33.33%) was anemic, and two respondents (66.7%) were not anemic. The Chi-Square test analysis results show that the calculated X2 value > X2 table is 7.236 > 3.841. This study concludes that there is a relationship between the duration of IUD use and Hb levels in IUD acceptors in the Tanah Kalikedinding Health Center work area in 2020. It is expected that health workers will check Hb levels at the start of IUD insertion and during acceptors' return visits and give Fe tablets to acceptors Kb long-term IUDKeywords        : duration, IUD use, haemoglobin level